Why Do We Need History Teaching (Learning) in Lithuanian Schools? Analysis of the Aims in the Contexts of Theoretical Didactics - Šermukšnytė, Rūta (Lietuvos istorijos studijos, 2017)
The goal of this article is to analyze the aims of history teaching (learning) in today’s Lithuanian general education schools in the contexts of ideas that are developed in theoretical didactics. The article, in accordance with foreign literature, the existing Lithuanian history education programs and public debates concerning the problem of the teaching of history in Lithuanian secondary schools, tries to answer the following questions: What history teaching aims or orientations in general can be legitimate in societies at the junction of the 20th–21th centuries and why? How history teaching (learning) aims are defined in Lithuanian history education programs? Which of the history education (learning) aims are visible in the public debate of people who are not indifferent and who develop Lithuanian education policy and what are the exact reasons that cause the preference of these aims? How should the history teaching (learning) aims in Lithuania be valued in the perspective of ideas that are developed in theorethical didactics? The article begins with the classification of sources for aims (and the explication their legitimacy reasons) according to German history didactics specialist Joachim Rohlfes and Canadian researcher Peter Seixas. The second chapter focuses on J. Rohlfes’s classification in order to ephasize the problem of recognition of sources for Lithuanian history teaching (learning) aims (which are cited in the programs of history education), their inter-compatibility and implementation. The third chapter mainly focuses on Mr. Seixas’s concept concerning the identification of “gravity” directions in public debate and the implementation of the ideas in order to achieve the more diverse evaluation of the problems. The conclusions present research results and the remarks by the author of this article concerning the formation of the aims of history teaching (learning) in Lithuanian general education schools.